2014
DOI: 10.5194/hess-18-305-2014
|View full text |Cite
|
Sign up to set email alerts
|

Addressing drought conditions under current and future climates in the Jordan River region

Abstract: Abstract. The Standardized Precipitation-Evaporation Index (SPEI) was applied in order to address the drought conditions under current and future climates in the Jordan River region located in the southeastern Mediterranean area. In the first step, the SPEI was derived from spatially interpolated monthly precipitation and temperature data at multiple timescales: accumulated precipitation and monthly mean temperature were considered over a number of timescalesfor example 1, 3, and 6 months. To investigate the p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
53
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(58 citation statements)
references
References 56 publications
5
53
0
Order By: Relevance
“…Finally, we note that we are using a meteorological drought index (SPEI) and simulate population exposure to SPEI < −2 (Bextreme drought^) (Centre for Ecology and Hydrology 2016; Törnros and Menzel 2014). Although SPEI's long time scales (e.g., 24 months) are related to variations in groundwater storage (Vicente-Serrano et al 2009), a comprehensive assessment of drought impacts may, nevertheless, require hydrology-related drought indices (Maskey and Trambauer 2015) and a study of groundwater resources (Green et al 2011).…”
Section: Modeling Exposure To Extreme Droughts In the Futurementioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we note that we are using a meteorological drought index (SPEI) and simulate population exposure to SPEI < −2 (Bextreme drought^) (Centre for Ecology and Hydrology 2016; Törnros and Menzel 2014). Although SPEI's long time scales (e.g., 24 months) are related to variations in groundwater storage (Vicente-Serrano et al 2009), a comprehensive assessment of drought impacts may, nevertheless, require hydrology-related drought indices (Maskey and Trambauer 2015) and a study of groundwater resources (Green et al 2011).…”
Section: Modeling Exposure To Extreme Droughts In the Futurementioning
confidence: 99%
“…In the present paper, we calculate the accumulated difference between P and PET in the previous 24 months. To capture the frequency and duration of drought, we define Bextreme drought^as the environmental condition for SPEI < −2, a common threshold value (Centre for Ecology and Hydrology 2016; Potop et al 2013;Törnros and Menzel 2014). This condition may cause devastating social impacts through crop and pasture losses, health and extreme fire risks (Svoboda et al 2002).…”
mentioning
confidence: 99%
“…Precipitation over Jordan is highly variable in space and time [2,16,46]. According to Mohsen [2], precipitation varies from 6000 to 11,500 million m³/year.…”
Section: Blue Water Scarcity: Actual Versus Maximum Sustainable Blue mentioning
confidence: 99%
“…Based on model simulations for different climate change scenarios, Abdulla et al [18] found that decreases in precipitation will lead to significant decreases in runoff and groundwater recharge in the Zarqa river basin (Figure 1). The percentage of time that the Jordan River basin and its surroundings will experience moderate, severe, and extreme drought conditions is expected to increase in the future [16]. Such droughts can have devastating effects when the agricultural and water management practices in place are unsustainable [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation